Development of interoception: the critical role of maternal affective touch in early attachment - Solano Durán, Paola; Isaac, Valeria (Frontiers in Neuroscience, 2026)
Despite growing interest in interoceptive functioning, primarily due to its pivotal role in physical and mental health, little is known about its developmental origins and the factors that influence it. Interoception—the perception of one’s internal bodily state—in which bottom-up sensory signals from receptors located in the body are integrated with top-down cognitive interpretations, is crucial for homeostatic and emotional regulation and overall wellbeing. Specific questions remain on how and when this function typically develops. Here, we propose that early attachment relationships, facilitated by maternal affective touch (MAT), provide a critical context in which interoceptive signals are integrated within central nervous system structures and learned to be accurately sensed, perceived, and interpreted later in life. We examine neurobiological mechanisms linking MAT to interoceptive pathways by integrating perspectives from attachment theory and interoception research. We argue that relational experiences and embodied interactions in infancy lay the foundation for lifelong interoceptive awareness and adaptive functioning. These perspectives have implications for developmental models of interoception and for translational approaches to psychopathology characterized by interoceptive and autonomic dysregulation, suggesting that early relational and embodied processes may represent important targets for future research and intervention.